Black Slavonian pig – a breed for extensive husbandry (A review) - Károlyi, Danijel; Luković, Zoran; Salajpal, Krešimir; Đikić, Marija (Acta Agraria Kaposváriensis, 2010)
Black Slavonian (BS) pig is local Croatian breed originated in Slavonia region in the second half of the 19th century. Until the 1950s it was the most widespread breed in Slavonia, mainly used for the production of fat and meat products. Later, its population was drastically reduced and in 1990s the survival of the breed was endangered. In order to halt breed decline the State introduced protection measures which resulted in population increase; in 2008 there were 78 boars and 669 sows. The breed is well adapted for traditional outdoor keeping which includes the utilization of pasture and woodland with supplement of a small amount of grains. Litter size is low with ~ 1.5 farrowing per year per sow. The fattening abilities are also modest, with low daily gains and high share of fat in the carcass. However, the meat quality is good, with high content of intramuscular fat and high appreciation of its meat products. As a part of current trends of support of sustainable and traditional food production systems, it becomes important to preserve the production systems of BS pigs and their products. Development of marketing of niche products could be the best way for long-term preservation of breed.
Keywords: pigs; breeds; Black slavonian pig; production traits